A colonização e a economia açucareira em Campinas, 1765 a 1829 - Teixeira, Paulo Eduardo [UNESP] (Universidade Estadual Paulista Julio de Mesquita Filho, 2020)
From the expansion of sugarcane in West São Paulo during the late eighteenth and early nineteenth centuries, the settlement in that region started to transform the State of São Paulo, intensifying the human presence in the countryside region. The arrival of a population of free people and slaves was the result of a broad process in which economic, political, and social factors brought significant changes to the region, making it the main axis of São Paulo economy based on slavery. In order to evaluate the impact of that colonization process, our goal was to study the demographic structures and slave ownership in Campinas, from 1765 to 1829, using as main documentary source the Nominative Lists of inhabitants.

A partir da expansão da lavoura canavieira em São Paulo durante o final do século XVIII e início do século XIX, o povoamento do Oeste foi transformando a fronteira do interior paulista, intensificando a presença humana nessa região. A chegada de pessoas livres e escravas foi o resultado de um processo amplo, em que fatores econômicos, políticos e sociais trouxeram mudanças significativas para a região, transformando-a no eixo principal da economia escravista de São Paulo. A fim de avaliarmos o impacto desse processo colonizador, nosso objetivo foi estudar as estruturas demográficas e a posse de escravos em Campinas, de 1765 a 1829, utilizando como principal fonte documental as Listas Nominativas de habitantes.
Colonization and the Sugar Economy in Campinas, 1765 to 1829
Keywords: Settlement; Slavery; Aggregate; Historical Demography; São Paulo; Povoamento; Trabalho escravo; Agregado; Demografia Histórica; São Paulo